2017
DOI: 10.1007/s00464-017-5840-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach using the enhanced-view totally extraperitoneal (eTEP) technique for laparoscopic retromuscular hernia repair

Abstract: Our initial multicenter evaluation of the eTEP access technique for ventral and incisional hernias has found the approach feasible and effective. This novel approach offers flexible port set-up optimal for laparoscopic closure of defects, along with wide mesh coverage in the retromuscular space with minimal transfascial fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
2
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(210 citation statements)
references
References 24 publications
3
172
2
21
Order By: Relevance
“…• Mesh placement outside of abdominal cavity represents a huge advantage, avoiding the contact between the mesh and the viscera (with the all late consecutives complications) and, on the other hand, reducing the cost (quite high cost of dual meshes and fixation devices). • The early results of this procedure were published in Surgical Endoscopy (14) and show the superiority then "traditional" laparoscopic approach (IPOM) regarding pain, recovery, recurrence, cost. • My personal experience is 63 cases in the last 18 months.…”
Section: Results Conclusionmentioning
confidence: 99%
“…• Mesh placement outside of abdominal cavity represents a huge advantage, avoiding the contact between the mesh and the viscera (with the all late consecutives complications) and, on the other hand, reducing the cost (quite high cost of dual meshes and fixation devices). • The early results of this procedure were published in Surgical Endoscopy (14) and show the superiority then "traditional" laparoscopic approach (IPOM) regarding pain, recovery, recurrence, cost. • My personal experience is 63 cases in the last 18 months.…”
Section: Results Conclusionmentioning
confidence: 99%
“…Several novel extraperitoneal techniques have been developed to perform retromuscular repair through minimally invasive methods, including mini/ less open sublay (MILOS) repair [9], followed by modified Fig. 7 Placement of a 15 × 9-cm 2 self-gripping mesh in the extraperitoneal space (a case of umbilical hernia) MILOS surgery with endoscopic assistance (e-MILOS) [10], laparoscopic transabdominal retrorectus repair [11], endoscopic transabdominal midline reconstruction technique facilitated by endoscopic linear stapling [12], completely endoscopic sublay dissection methods including the enhanced-view totally extraperitoneal (eTEP) technique initiated by Belyansky et al [13], and the TES repair technique reported by our team [2].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, in an epigastric hernia that is extremely close to the xiphoid process, a long distance extraperitoneal dissection from the suprapubic area to the xiphoid area will require a lot of dissection and seems to be unreasonable. In these cases, some surgeons recommend the transabdominal approach to enter the preperitoneal space [6]; however, an e-MILOS or eTEP technique seems to be more appropriate in this scenario than any other techniques [10,13]. For a congenital lumbar hernia that is herniated from the superior lumbar triangle (Grynfeltt hernia), a retroperitoneal endoscopic approach can be utilized to achieve extraperitoneal repair [25].…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons were the great technical di culty of the procedure and the long operative time. However, this situation has changed in the last 2 years, as many articles about this emerging technique from different countries have been published (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%